Soil Testing for Plant-Available Nutrients—What Is It and Why Do We Use It? - George Hochmuth; Rao Mylavarapu; Ed Hanlon (EDIS)
Farmers need soil-testing procedures to assess soils for potential plant-available nutrients. Soil testing is the foremost best management practice (BMP). It helps farmers achieve profitable crops while protecting the environment from excessive fertilization and nutrient losses. This 5-page fact sheet describes the important steps required to test soil for potential plant-available nutrients. Written by George Hochmuth, Rao Mylavarapu, and Ed Hanlon, and published by the UF Department of Soil and Water Science, October 2014.